2016
DOI: 10.1186/s12968-017-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance evaluation of symptomatic severe aortic stenosis: association of circumferential myocardial strain and mortality

Abstract: BackgroundIt is unknown whether circumferential strain is associated with prognosis after treatment of aortic stenosis (AS). We aimed to characterise strain in severe AS, using myocardial tagging cardiovascular magnetic resonance (CMR), prior to and following Transcatheter Aortic Valve Implantation (TAVI) and Surgical Aortic Valve Replacement (SAVR), and determine whether abnormalities in strain were associated with outcome.MethodsCMR was performed pre- and 6 m post-intervention in 98 patients (52 TAVI, 46 SAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
1
27
0
2
Order By: Relevance
“…Patients with severe AS and preserved LVEF in our cohort exhibited lower-than-normal GLS, a finding consistent with that found in several prior studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In patients with severe AS, the increased afterload may lead to left ventricular hypertrophy, decreased coronary perfusion, subendocardial ischemia, and eventually myocardial fibrosis [3,4].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with severe AS and preserved LVEF in our cohort exhibited lower-than-normal GLS, a finding consistent with that found in several prior studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In patients with severe AS, the increased afterload may lead to left ventricular hypertrophy, decreased coronary perfusion, subendocardial ischemia, and eventually myocardial fibrosis [3,4].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, 3-dimensional (3D) speckletracking echocardiography could provide a more precise representation of myocardial deformation [12]. New insights into LV remodeling and myocardial deformation could potentially improve our ability to identify patients with aortic stenosis who are at highest risk for adverse remodeling or early LV dysfunction [13][14][15][16][17][18]. However, few studies have comprehensively characterized myocardial deformation in patients with severe aortic stenosis by 3D speckle-tracking echocardiography [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Musa et al (27) showed that transcatheter aortic valve implantation and surgical aortic valve replacement procedures were associated with comparable declines in rotational LV mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Al Musa et al 12 demonstrated that patients with severe AS had a significantly worsened longitudinal and circumferential strain values compared to controls, which also correlated with the postoperative functional recovery and clinical outcome. 71 Interestingly patients with severe AS and no or mild symptoms demonstrate a comparable reduction in circumferential and longitudinal strain to those with significant symptoms. 12 Current guidelines recommend valvular replacement mainly for patient with symptomatic severe valvular disease, or LV function impairment.…”
Section: Prognostic Implication Of Cmr: Fibrosis Equates With Prognosismentioning
confidence: 94%
“…A more important role of CMR in the selection of patients for valve replacement would be helpful for recognizing those who would benefit from AVD correction, even in terms of clinical outcome and LV reverse remodelling. 10,71 However, in clinical practise, the use of CMR in pre-surgical planning is still marginal in many centers, a secondary choice compared to echocardiogram and CTA, generally limited to selected cases (young patients or those with renal failure).…”
Section: Pre-procedural Planningmentioning
confidence: 99%